The role of macrophages in the mitigation by decitabine of acute allograft rejection - Daccarett-Bojanini, William N.; Sollmann, Manuel; Yarnoff, Kristine M.; Heller, Nicola M.; Dodd-o, Jeffrey M. (Frontiers in Transplantation, 2025)
IntroductionWe have recently shown that the DNA hypomethylating agent decitabine (DAC) rescues lung allografts from acute rejection. This involves a mechanism that is dependent on host CD4+ FoxP3+ T cells for maximal benefit. DAC treatment also reduces host T-cell IFN-γ production. We therefore hypothesized that DAC may also reduce host macrophage activation. Our objective was to determine if an effect on macrophages contributes to the beneficial effects of DAC in transplantation.MethodsIn murine orthotopic lung transplant, hosts were treated on post-op day 3-8 with Clodronate (n = 5), DAC (n = 9), or DMSO (n = 11).ResultsPartial macrophage depletion (clodronate) improves allograft gross and histologic integrity. DAC-mediated allograft rescue was associated with reduced host macrophage recruitment into allograft airways, reduced activation of recruited macrophages, and regeneration of donor resident alveolar macrophages.DiscussionThese findings suggest that infiltrating host macrophages promote allograft rejection. They also suggest that donor alveolar health is indicative and/or promoting of allograft tolerance.